Análisis de la estrategia de campaña de Lenín Moreno hasta su discurso de posesión - Parra Barragán, Angela Yesenia (2018)
How, despite an adverse political conjuncture, corruption scandals and the natural wear and tear of the ruling party, the ruling-party candidate, Lenín Moreno, could achieve the electoral victory? To what extent does the implementation of specific political marketing strategies, during the campaign period, modify electoral behavior? The framing of the electoral strategy was built on political spots, political advertising, political rhetoric and the candidate’s image management. The image management considered a positioning and reinforcement of the candidate’s image during his vice presidential term: subject of reconciliation and grantor of hope. These elements allowed the pro-government candidate to gain the electoral victory. Additionally, the communication of a message with simple elements that have a deep impact in the electorate, which nominated Moreno as the leader and continuer of Rafael Correa’s project. The current investigation intends a different approach. It evaluates the tactical selection of an electoral campaign strategy for each of the ballots, particularly, the employment of spots, which positioned Lenin Moreno and endorsed the ruling-party candidate to acquire the victory.